Comparative study: The governance models of islamic microfinance institutions in Indonesia and Bangladesh for sustainable social-economic impact - Jihan Arlista Putri; Amin Wahyudi (Faculty of Islamic Economics and Business UIN Salatiga, 2025)
Islamic Microfinance Institutions (IMFIs) play a pivotal role in promoting inclusive socio-economic development by integrating ethical finance with Shariah-based principles. This research investigates the governance models and socio-economic impact of IMFIs in Muslim-majority countries, focusing on Indonesia and Bangladesh. Using a qualitative, library research method, data were synthesized from secondary sources such as journals, government reports, and institutional publications spanning 2015–2025. The analysis explores key governance elements including institutional structures, leadership patterns, Shariah compliance mechanisms, and performance accountability. Findings indicate that while both countries implement faith-driven financial models, their governance approaches are context-specific, shaped by structural, cultural, and regulatory dynamics. However, comparative clarity is limited, as the study does not provide systematic cross-national performance metrics. Despite this, the role of IMFIs in financial inclusion and women’s empowerment is evident, particularly through instruments like zakat, qard hasan, and group-based financing. This research underscores the importance of maqāṣid al-sharīʿah in strengthening ethical governance and recommends policy alignment to enhance institutional sustainability and social impact.